Association between socio-demographic profile and severity of cognitive impairment in elder patients presenting with new onset of psychiatric symptoms: a cross sectional study - Antony, Jery; Nakulan, Anisha; John, Shiny (International Journal of Research in Medical Sciences, 2019)
Background: Cognitive impairment in the elderly is a common condition and, in most instances, primary care providers are the first point of contact for a patient and family. This study was aimed to find out the association between socio-demographic profile and severity of cognitive impairment in elder patients presenting with new onset of psychiatric symptoms. Methods: A cross sectional study was done among elder subjects (≥60 years of age) presented with new onset of psychiatric symptoms during one year period. A structured questionnaire was used to assess the socio-demographic details such as age, sex, education, occupation, socio-economic status and marital status. Mini International Neuropsychiatric interview and Montreal Cognitive Assessment scale were used for psychiatric diagnosis and severity of cognitive impairment grading, respectively. Association between socio-demographic data and cognitive impairment was statistically analyzed. Results: Among the 67 subjects included in the study, 76.2% had cognitive impairment. Majority of the subjects were females (56.7%) in the age group of 66-70 years. The association between cognitive impairment and sex (p=0.006), education (p=0.002) and occupation (p=0.015) were significant. But no significant association between cognitive impairment and marital status (p=0.0137) or socioeconomic status (p=0.400) was evidenced. Conclusions: Females in the age group of 66-70 years were more prevalent to cognitive impairment. The association between sex, education, occupation and severity of cognitive impairment was significant. No significant association between severity of cognitive impairment score and marital status or socioeconomic status was found.